2019
DOI: 10.1177/1533317519827416
|View full text |Cite
|
Sign up to set email alerts
|

Specific Association Between Religiosity and Cognitive Functions in Alzheimer’s Disease

Abstract: Objectives: This study aimed to identify the specific relationship between subdomains of religious variables and cognitive functions in outpatients with Alzheimer's disease (AD). Methods: We recruited 325 patients with AD from a psychiatry outpatient clinic. The Korean version of the Consortium to Establish a Registry for Alzheimer's Disease and the Duke University Religion Index were used to assess cognitive functions and religiosity. We performed structural equation modeling and partial correlation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The associations between different aspects of religiosity and dementia observed in this study are consistent with prior research, which has identified a potentially protective effect of specific religious behaviors or practices on the onset and progression of dementia in general and AD in particular [ 9 - 11 ]. In other words, practices such as daily prayer or meditation, rather than membership status in a particular religious denomination, may have a greater and more significant protective effect.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The associations between different aspects of religiosity and dementia observed in this study are consistent with prior research, which has identified a potentially protective effect of specific religious behaviors or practices on the onset and progression of dementia in general and AD in particular [ 9 - 11 ]. In other words, practices such as daily prayer or meditation, rather than membership status in a particular religious denomination, may have a greater and more significant protective effect.…”
Section: Discussionsupporting
confidence: 91%
“…For example, affiliation with specific religious groups has been associated with a reduced risk of AD [8], while engagement in specific religious behaviors, such as daily prayer, has been associated with a reduced risk of cognitive decline at a later age [9]. Similarly, studies of patients with AD have found that religious activity is associated with better functioning in cognitive domains such as memory, language and constructional abilities, as well as with a slower rate of cognitive decline [10,11]. Two significant questions arise from an analysis of this research.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Nagpal et al 36 F I G U R E Preferred reporting items for systematic reviews and meta-analyses (PRISMA) selection of articles for review 26 of prayer or meditation, and subjective rating of how religious/spiritual the person is. Jung et al 37 and Kaufman et al 38 both used the DUREL, which another study adapted for the Korean population. 42 The DUREL includes five items with three subscales: (1) organizational religious activity, which measures frequency of religious attendance at meetings and activities;…”
Section: Centrality Of Religion/spiritualitymentioning
confidence: 99%
“…We identified 17 R/S measures in the 14 reviewed studies. The four studies that measured religiosity 35–38 used three different instruments: a 3‐item author‐created scale, 36 the Duke University Religion Index (DUREL), 39 and the Behavioral Religiosity Scale (BRS) 40,41 . Nagpal et al 36 .…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Older Latinxs face potentially distinctive risk factors for ADRD such as structural assimilation [5] and might have potential resilience factors like familial and other relationships, and religiosity or spirituality. Given that previous research has shown those factors to be associated with healthy aging [6] and cognition [7], a greater understanding of their role in ADRD among older Latinxs is warranted. Furthermore, studies explicitly focused on older Latinxs can characterize the diversity among older Latinxs in relation to ADRD and address an urgent public health need [8].…”
Section: Introductionmentioning
confidence: 99%